Strengthening Character Education Through School Culture in The New Normal Era: A Case Study at Al-Karim Lampung Basic Natural School - Trio Saputra; Dasim Budimansyah (Basic and Applied Education Research Journal, 2021)
Strengthening character education in schools is a government policy as an effort to re-put character as the core of education. The process of teaching and learning activities is currently carried out online and face-to-face while still prioritizing health protocols due to the pandemic. So, currently schools are required to continue to innovate in order to maximize the character education process in schools. The purpose of this study is to describe the strengthening of character education through school culture, the obstacles and efforts made during the pandemic. This research uses descriptive qualitative research. Data collection techniques using observation, interviews, and documentation. The research location was conducted at Alam Al-Karim Elementary School, Lampung. The research subjects are the Principal, Deputy Principal and Teachers. Based on the results of the research, strengthening character education through school culture is carried out in the form of habituation activities namely, Morning Activity, Daily Worship, Murajaah Qur'an, and Green Therapy as a means of socializing character values ​​and awareness to maintain health and mentally facing a pandemic. The obstacles are the limited time available and limited physical communication. The effort made by the school is through making a special curriculum in the new normal era. The conclusion of this research is that strengthening character education through school culture in the middle of a pandemic carried out by the Alam Al-Karim Elementary School is an alternative concept that can be applied in order to make character education effective as an important goal in education.